The effectiveness of a nurse-delivered breast health promotion program on breast cancer early detection behaviors - Anita Anita; Nelly Indrasari; Purwati Purwati; Ratna Aryani (Malahayati International Journal of Nursing and Health Science, 2021)
Background: Reported in Lampung Province, the prevalence of breast cancer cases has increased from 0.02% in 2010 to 0.7% in 2013. There were 1.030 cases. Two, Districts with the largest cases of breast cancer are west Lampung  (10%) and Pringsewu (9.8%).Purpose: To knowing the effectiveness of a nurse-delivered breast health promotion models on breast cancer early detection behaviors among women of childbearing period age.Methods: A quantitative study, the population were women of childbearing period age, and samples comprise 120 participant divided in four groups in each group consist 30 participant. 90 participant as intervention group and 30 participant as control group.  Independent t test was used in data analysis.Results: Shows there was no effect of education face to face with the booklet media and education face to face with the detection media cards, but there is a different result with education face to face with the combination of booklet and detection cards (p=0.004 mean difference= 0.767) on the behavior of early detection of breast cancer.Conclusion: The health practitioners should provide booklets together with the provision detection card to carry out routinely in preventive efforts. The study also recommends further research on active networking efforts and the efforts of palliative care for those diagnosed with breast cancer.